Oxytocin changes in women with emergency cesarean section: Association with maternal blues by delivery mode - Eri Shishido; Shigeko Horiuchi (Heliyon, 2023)
Introduction: Women with emergency cesarean section (CS) have presumed effects of an unscheduled surgery on their salivary oxytocin (OXT) level and psychological state. This study aimed to measure changes in the salivary OXT levels of women with emergency CS and change in the OXT levels by delivery mode, and to investigate the association between changes in OXT levels and maternity blues. Methods: We used a longitudinal observational study. The eligibility criteria were primipara pregnant women who were planning to have vaginal delivery. The salivary OXT levels of women were measured at 36 weeks gestation, 38 weeks gestation, 1 day postpartum, and 5 days after childbirth. Maternity blues was diagnosed using the Maternity Blues Scale (13 items), ‘Fatigue after Childbirth’ was diagnosed using the Visual Analogue Scale (0–100), and the subjective symptoms of fatigue was diagnosed using the Jikaku-sho shirabe. The three groups (“Without EA”, “With EA”, and “Emergency CS”) were analyzed separately. The changes in the oxytocin levels of women with emergency CS at four time points were analyzed by using a repeated measure analysis of variance. Results: The mean OXT levels of women with emergency CS (n = 6) were significantly lower at 5 days after childbirth than at 36 weeks gestation, 38 weeks gestation, and 1 day postpartum. There was a significant middle correlation between changes in the mean maternity blues scores between 1 day and 5 days, and the mean changes in OXT levels from 38 weeks gestation to 5 days after childbirth. Conclusion: It could be assumed that women with emergency cesarean section may be affected psychologically by the unplanned method of delivery. In the present study, it was not possible to analyze this association because of the small sample size; however, it is possible to clarify predictors as the sample size accumulates in the future.